Inventing new uses for tools: A cognitive foundation for studies on appropriation - Salovaara, Antti (Human Technology, 2008)
Appropriation refers to the processes that take place when new uses are invented for tools and when these uses develop into practices and start spreading within a user community. Most research in human-computer interaction and computer-supported cooperative work to date has studied this phenomenon from a social sciences approach, thus focusing on the practice side of the phenomenon. This paper addresses appropriation from the other direction, drawing from ecological psychology and focusing on cognitive processes in context. Appropriation from this perspective is understood as an interpretation process in which the user perceives in a tool a new opportunity for action, thus acquiring a new mental usage schema that complements the existing uses. This approach highlights the need to study how schemata are put into use and how they evolve through new interpretations. Ensuing research questions are presented together with three strategies of applying the new approach in system design.